Human systems integration to enhance maritime domain awareness for port/harbour security - Shahbazian, E. (Elisa); Rogova, Galina (NATO science for peace and security series. Information and communication security, 2010)
The multidisciplinary Advanced Research Workshop (ARC) entitled "Human Systems Integration to Enhance Maritime Domain Awareness for Port/Harbour Security" brought together experts in the domains of Harbour/Port Security and Human Factors, as well as Knowledge Management, Knowledge Exploitation and Decision Support Technologies from the NATO, NATO Partner and Mediterranean Dialogue Countries, who presented and discussed various aspects of the problems of enhancing Maritime Domain Awareness in Harbours/Ports through application of Human-System Integration and advanced technologies